English Language Education at the SSC level in Bangladesh: Examining the Teaching Methodology - Khatun, Ayesha (English Language in Focus (ELIF), 2022)
The study was designed to examine the teaching methodology used for English education at the SSC level of education in Bangladesh which aimed to produce competent learners who could meet the 21st century’s globalized demand of effective and continuous communication. The study proposed here is based on both descriptive and contextual methods. To collect data and address the research questions the learner questionnaire, the teacher questionnaire with the support of a personal in-depth interview method has been used. In the study, data were collected from 40 students and 10 teachers from the SSC level, who are randomly selected from both rural and urban areas. The result found that “English for Today” is designed to practice the CLT approach but it is not used properly and effectively. The analysis of the data revealed that teachers taught English by practicing and solving model questions from guidebooks using GTM so that learners could secure high scores in the examination. The materials of the CLT approach are taught in the Grammar-Translation method (GTM). Thus, this teaching methodology fails to produce competent learners. A Broader perspective with more samples at various locations will add more value to the idea.